Teologi Terapan dalam Islam: Sebuah Syarah Hadis dengan Pendekatan High Order Thinking Skill - Wahyudin Darmalaksana; Bambang Qomaruzzaman (UIN Sunan Gunung Djati Bandung, 2020)
This study aims to discuss the high order thinking skill approach in the sharah hadith method with regard to contemporary issues for the formulation of applied theology. This research method uses a qualitative type through literature study by applying the high order thinking skill approach. The results and discussion of this research include sharah hadith about kalam, tauhid science to applied theology, and from theology to service according to the high order thinking skill approach. The conclusion of this study is that the high order thinking skill approach allows being applied in the sharah hadith method with regard to contemporary issues for the formulation of applied theology. This study recommends the urgency of applying high order thinking skills as a research approach to contemporary issues in Islamic diversity.